ILLICIT DRUGS: CHALLENGES AND TENACITIES - Imam, Syed Kaleem; Fatima, Samza (Journal of Pakistan Psychiatric Society, 2022)
This paper examines the global phenomenon of drug addiction, analyzes the historical trajectory of drug abuse, examines its categories, and considers response mechanisms in conjunction with local and international initiatives intended to reduce substance abuse. The paper emphasizes the role of legal institutions at the local level and the way international actors and stakeholders collaborate to curb the threat. The research presented here presents opportunities for drug control through programs, rehabilitation sessions, and policy initiatives. It sketches a comprehensive and well-defined program that focuses on the role of legal institutions in preventing and treating drug addiction. It explores the challenges of drugs as a global hazard and provides policy frameworks for collective responses in place of government and non-government interventions. In this study, a doctrinal approach is employed along with an exploratory approach. This paper would contribute considerably to the understanding of the subject.